(untitled) (Medical Forum Monthly, 2020)
Objective: The aim of this study is to determine the incidence of placenta previa along with its risk factors in Gynecology/obstetrics unit of Ayub teaching hospital, Abbottabad. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the The study was conducted in Gynaecology / Obstetrics department ATH, Abbottabad, KPK from November 2018 to November 2019. Materials and Methods: All pregnant women having POG > 28 weeks were included in the study; those unsure of dates or diagnosed with eclampsia were excluded. Sample size was 426 and data was analyzed using SPSS version 23. A p-value of ≤ 0.05 was considered statistically significant for association between categorical variables. Results: The frequency of placenta previa was found to be 6.3%. The mean age was 26.33 ± 5.36 years. Mean parity was 1.44±1.57 and mean gravida was 2.92±2.13. 22.2% of the pregnant women with placenta previa had a history of previously diagnosed placenta previa (p-value=0.047). 33.3 % of patients diagnosed with placenta previa had a history of abortion (p-value=0.51). 55.6% of the patients diagnosed with placenta previa were grand multigravida followed by multigravida (44.4%) whereas there were no primigravida (p-value=0.01). 77.8% of the patients diagnosed with placenta previa were multiparous followed by primiparous (22.2%), whereas there were no nulliparous women patients (p-value= 0.029). Conclusion: The frequency of placenta previa was 6.3% which is abnormally high. History of previous placenta previa, gravida and parity were found to be major risk factors for placenta previa. History of previous caesarean section and age were also associated with placenta previa but were statistically insignificant.